"Normal" TEWL‐how can it be defined? A systematic review. Issue 10 (31st July 2022) - Green, Maxwell; Feschuk, Aileen M.; Kashetsky, Nadia; Maibach, Howard I.
Abstract: Trans‐epidermal water loss (TEWL), the total non‐eccrine sweat water evaporating from a given area of epidermis over time, is a measurement of skin barrier integrity. Skin diseases (e.g., psoriasis and atopic dermatitis) often result in transient increases in TEWL, so, knowledge of "normal" TEWL values may be used to predict disease progression in dermatological settings. Variables such as age, race and anatomic location have been suggested to affect TEWL, but current regulatory agencies have failed to control for additional variables of interest. Thus, this review summarizes variables that may cause TEWL variation. A comprehensive literature search was performed using Embase, PubMed and Web of Science to find human studies that provided data on variables affecting TEWL. 31 studies, analysing 22 affecting TEWL, were identified. Variables causing increased TEWL were mask‐use ( n = 1), dry eye disease ( n = 1), chronic venous disease ( n = 1), coronary artery disease ( n = 1), age (infants vs adults) ( n = 4), nourishment in infants ( n = 1), stress within individuals ( n = 2), Body Mass Index ( n = 2), bathing versus showering ( n = 2) and scratching/friction ( n = 1). Variables with decreases in TEWL were genetic variability with SNPs on chromosome 9q34.3 ( n = 1) and cancer‐cachexia ( n = 1). We summarized 12 variables that impact TEWL and are not typically controlled for in experimental settings. Therefore, defining normal TEWL may currently be problematic. Thus, regulatory agencies should provide stricter guidelines on proper measurement of TEWL to minimize human introduced TEWL variation, and we should continue to examine factors impacting individual skin integrity.